Complement-dependent cytotoxicity of human autoantibodies against myelin oligodendrocyte glycoprotein - Kohyama, Kuniko; Nishida, Hiroya; Kaneko, Kimihiko; Misu, Tatsuro; Nakashima, Ichiro; Sakuma, Hiroshi (Frontiers in Neuroscience, 2023)
Background The autoantibody to myelin oligodendrocyte glycoprotein (MOG), a component of the central nervous system myelin, has been identified in a subset of demyelinating diseases. Although MOG protein has been postulated as a candidate autoantigen in human demyelinating disorders, there is no convincing evidence to support the direct pathogenic contribution of this autoantibody. Objective To elucidate the role of anti-MOG autoantibodies in human demyelinating disorders, we assessed the effect of autoantibodies on MOG-expressing cells. Methods Mammalian cells expressing the human MOG protein reacted with human anti-MOG autoantibodies in the presence or absence of complement. Results Anti-MOG-positive sera, but not -negative sera, caused cell death in MOG-expressing cells. There was a significant correlation between anti-MOG antibody titer and cytotoxicity in MOG-expressing cells. This cytotoxic effect depended on the complement because it disappeared after heat inactivation of sera. Importantly, anti-MOG IgG and externally added complement were necessary for sufficient cytotoxic effects. Anti-MOG autoantibodies were histologically colocalized with complement and formed a membrane attack complex consisting of anti-MOG IgG and complement factors. Conclusion Although anti-MOG antibodies have cytotoxic activity, it is unlikely that these antibodies cause massive oligodendrocyte death in vivo due to the insufficient amount of complement to fully activate complement-mediated cytotoxicity.